Social capital and banking system profitability: A survey of European Union countries (European Journal of Government and Economics, 2019)
Over the last years, the concept of social capital as a facilitator of economic activities has been a remarkable issue among economists. In this article, we study the impact of social capital on banking performance focusing on profitability in the European Union for period 2008-2016. Social capital indicators are applied in the model are "trust in others" and "fair behavior of others". We expect more profitable banks in societies with higher levels of social capital. According to the type of data, we apply GMM estimator to do more efficient estimations. We use auxiliary variables such as bank asset, capital adequacy, real interest rate, the cost to income ratio as micro variables, GDP and inflation are employed as macros. Our estimations point at a rejection of the main hypothesis. Opportunistic behavior and less social trust result in more profits for European countries. We justify the results in two ways. First, due to the 2008 financial crisis, trust in all institutions has decreased in European countries. The second reason concerns countries with low levels of social capital. The decrease of trust for the banking system is lower than for other institutions. Therefore, that sector may benefit is such circumstances.